Preventing Exertional Death in Military Trainees: Recommendations and Treatment Algorithms From a Multidisciplinary Working Group. Issue 4 (1st April 2016) - Webber, Bryant J.; Casa, Douglas J.; Beutler, Anthony I.; Nye, Nathaniel S.; Trueblood, Wesley E.; O'Connor, Francis G.
ABSTRACT: Despite aggressive prevention programs and strategies, nontraumatic exertional sudden death events in military training continue to prove a difficult challenge for the Department of Defense. In November 2014, the 559th Medical Group at Joint Base San Antonio-Lackland, Texas, hosted a working group on sudden exertional death in military training. Their objectives were three-fold: (1) determine best practices to prevent sudden exertional death of military trainees, (2) determine best practices to establish safe and ethical training environments for military trainees with sickle cell trait, and (3) develop field-ready algorithms for managing military trainees who collapse during exertion. This article summarizes the major findings and recommendations of the working group.